SCHOOL ADMINISTRATORS' WORKING EXPERIENCE AND STUDENTS' ACADEMIC PERFORMANCE IN SENIOR SECONDARY SCHOOLS IN BAUCHI, DUTSE AND GOMBE STATES - ABDULLAHI, BARAKATU (American Journal of Education and Practice, 2021)
Purpose: This study investigated the School administrators' working experience and students' academic performance in senior secondary schools in Bauchi, Dutse and Gombe states of Nigeria. Methodology: The study adopted the descriptive research designed of the correlation type. Thirty (30) senior secondary schools administrators were selected and used as the respondents to this study, ten school administrators from each state. The instruments used to collect relevant data were school administrators' working experience check list and a self-designed questionnaire developed by the researcher, it was titled School Administrators' Working Experience and Students' Academic Performance (SAWESAP). The questionnaire was validated by two experts, one in the area of educational administration and planning, one in the measurement and evaluation both from Faculty of Education, Federal University, Kashere, Gombe State. Their suggestions and recommendations were incorporated into the final version and the reliability coefficient index of 0.73 was obtained after test-re-test with two weeks interval. Data collected were analysed using Statistical Package for Social Science (SPSS). One hypothesis was formulated and tested. Pearson Product Moment Correlation (r) Coefficient analysis procedure was used to test the hypothesis at 0.05 significant levels. Findings: The results of the analysis showed that, there was significant positive correlation between school administrators' working experiences and students' academic performance. Unique Contribution to Practice and Policy: Based on the findings, it was recommended among others that, school administrators' experience will be considered when it comes to placement and promotion of school administrators that would enable them perform maximally in managing and handling human and material resources.